(untitled) (Вісник: Міжнародні відносини, 2024)
The article analyzes the impact of new emerging relationships in financial markets across the world through analysis of new financial operations principles that emerged from such relationship. These principles include the further encouraging of the automation of financial transaction, supporting democratization of finance, self-governance of cryptocurrency exchanges and financial market participants. Such new features of financial market had irrevocably led to appearing of new issues, problems and challenges for law and financial market policymakers. Through analyzing deeply these features by comparing different legal ways to approach it, the possible solutions could be found. However, in no way such solution will be peculiar to only one country. As article demonstrates, all these principles are cross jurisdictional and govern the problems not for one country within its border, but for the essence of it itself that is without border and often without any physical realization. Herein the idea that takes place in these principles such as absence on intermediary, less bureaucracy and capital market not only for professionals should be regulated properly. Thus, the way to it is yet to be found, however understanding the essence of these new principles for financial market operations will help to found effective approach. Moreover, such effective approach may be based on FinTech, RegTech or SupTech that are also analyzed in this article.